2003
DOI: 10.1038/sj.onc.1206655
|View full text |Cite
|
Sign up to set email alerts
|

Noxa in colorectal cancer: a study on DNA, mRNA and protein expression

Abstract: Noxa is a BH3-only member of the Bcl-2 family, upregulated by p53 as a response to DNA damage. Mutations in the BH3-only region of other BH3-only members lead to an inactive protein. We have investigated the mRNA expression of Noxa with real-time PCR in 94 unselected colorectal adenocarcinomas and the corresponding normal mucosa. Among them, Noxa protein expression was investigated with immunohistochemistry in 16 tumors and six corresponding normal mucosa samples. Further, we searched for Noxa mutations in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Apoptosis induction in colorectal cancer cells by chemotherapy is partly (B50%) dependent on the induction of PUMA (Wang et al, 2007). Noxa is expressed both in the normal intestine and in most intestinal tumours (Jansson et al, 2003), and Noxa deficiency strongly reduces p53-dependent apoptosis in intestinal crypts following g-irradiation (Shibue et al, 2003). Our results show that Noxa also has an essential role in chemotherapy-induced KRAS/p53-dependent apoptosis induction in intestinal (colorectal) cancer cells.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Apoptosis induction in colorectal cancer cells by chemotherapy is partly (B50%) dependent on the induction of PUMA (Wang et al, 2007). Noxa is expressed both in the normal intestine and in most intestinal tumours (Jansson et al, 2003), and Noxa deficiency strongly reduces p53-dependent apoptosis in intestinal crypts following g-irradiation (Shibue et al, 2003). Our results show that Noxa also has an essential role in chemotherapy-induced KRAS/p53-dependent apoptosis induction in intestinal (colorectal) cancer cells.…”
Section: Discussionmentioning
confidence: 57%
“…However, such negative correlations are hard to interpret, given that Noxa induction in response to chemotherapy is transient. Colorectal tumours express Noxa at normal levels (Jansson et al, 2003), and inactivating mutations have so far not been reported. Therefore, the loss of Noxa function does not seem to be required during colorectal tumour development.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotide sequences of PCR primers were: TRAIL-R1-sense-5 CGATGTGGTCAGAGCTGGTACAGC-3 and antinsense-5 -GGACACGGCAGAGCCTGTGCCAT C-3 , 217 bp amplified fragment; TRAIL-R2-sense-5 -GGGAGCCGCTCATGAGGAAGTTGG-3 and antisense-5 GGCAAGTCTCTCTCCCAGCGT CTC-3 , 182 bp amplified product; 19 survivin-sense 5 AAG-AACTGGCCCTTCTTGGA-3 and antisense-5 CAA-CCGGACGAATGCTTTTT-3 , 147 bp amplified fragment; 20 NOXA-sense-5 GTCCGAGGTGCTCCA-GTT-3 and antisense-5 AAACGTGCACTCCCTG-AGA-3 (external primers) and sense-5 -GGGCTCTG-TCGCTGAG-3 and antisense-5 -TCGACCTCCTGAG-AAAACT-3 (internal primers) 226 bp amplified fragment; 21 Mcl-1-sense-5 CACGAGACGGTCTTCC-AAGGCATGCT-3 and antisense-5 -CTAGGTTGC-TAGGGTGCAACTCT AGGA-3 , 496 bp amplified product. GAPDH was used as housekeeping gene to control for loading.…”
Section: Rt-pcrmentioning
confidence: 99%
“…31). Similarly, NOXA expression was increased in 16% of colorectal tumors but was not associated with disease outcome (32). To date, neither NOXA nor PUMA has been studied in relation to PCa progression and clinical outcome.…”
mentioning
confidence: 99%